Exploring the Recent Social Security Pension Schemes of the Government of West Bengal: A Study of West Bengal, India - Samanta, Suteertha; Chakraborty, Aritra (South India Journal of Social Sciences, 2025)
In response to the significant aging population in West Bengal and the insufficient pension coverage for vulnerable groups, particularly older adults, the Government of West Bengal has implemented several social security pension schemes. This study investigates the awareness and utilization of these pension schemes and their impact on the elderly population in West Bengal. A representative sample of 220 older adults was selected using a stratified random sampling method that encompasses diverse caste groups. The research employed both quantitative surveys and qualitative in-depth interviews. Principal Component Analysis was conducted on selected indicators to assess the impact of these schemes on pensioners. The findings reveal that the pension schemes have generated positive outcomes for older adults, especially older women and individuals from economically disadvantaged backgrounds residing in rural areas. These schemes have improved mobility, increased self-esteem, fostered financial independence, and enhanced overall quality of life. Policymakers may consider leveraging these insights to formulate targeted strategies that promote increased awareness and utilization of these schemes, with a particular focus on reaching and supporting the most vulnerable segments of the elderly population. Such initiatives have the potential to significantly enhance individual well-being and contribute to the broader socioeconomic development of the community.